The Importance of Spiritual Need in Creating a New Spiritual Space (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Today, great importance is attached to raising a spiritually mature generation, perfect in all respects, and building an enlightened society. Strengthening the spiritual foundations of our society, developing the cultural and educational sphere has become an urgent issue. This article analyzes the issues of creating a new spiritual space in New Uzbekistan, the importance of spiritual needs.